Clinical Progression of COVID-19 Patient with Extended Incubation Period, Delayed RT-PCR Time-to-positivity, and Potential Role of Chest CT-scan - Erlina Burhan; Prasenohadi Prasenohadi; Rita Rogayah; Fathiyah Isbaniyah; Tina Reisa; Ibrahim Dharmawan (Acta Medica Indonesiana, 2020)
Coronavirus Disease 2019 (COVID-19), previously called 2019-nCoV, is a novel disease caused by SARS- CoV-2 which was first identified as outbreak of unknown respiratory illness in Wuhan, China. COVID- 19 was declared as global health emergency by WHO on March 11, 2020 and quickly elevated to global pandemic on 11 March 2020. COVID-19 symptom is highly various in each patient, with fever, fatigue, shortness of breath, and cough as the main presenting symptoms. Patient with COVID-19 may shows severe symptom with severe pneumonia and ARDS, mild symptom resembling simple upper respiration tract infection, or even completely asymptomatic. Approximately 80% of cases is mild. However the number may changes as more people are getting tested. Some experts are estimating that up to 50% of all cases may be asymptomatic carrier.